The impact of blockchain technology on customer attitude and behavioral intentions in the banking sector - Jayaraman, Gopu; Azad, Imran; Ahmed, Hanaa Mahmoud Sid; Hussien, Muawya Ahmed; Khan, Mohammed Shahfaraz (Asian Journal of Economic Modelling, 2023)
This study examines customer attitudes towards blockchain technology (BCT)-supported banking applications in Oman and explores the relationship between these attitudes and behavioral intentions, highlighting the influencing factors. Blockchain Technology (BCT) has disrupted the banking sector, but understanding customer attitudes towards BCT-supported banking applications and their impact on behavior remains limited. In pursuit of this objective, a quantitative research design was employed, involving the collection of data from retail bank customers in Oman through a structured questionnaire. The collected data underwent rigorous analysis using a robust Structural Equation Model, confirming the constructs' validity, reliability, and distinctiveness. The study uncovered that BCT has a positive impact on various aspects of the banking sector, including customer service quality, regulatory compliance, secured transactions, and cost reduction. By augmenting transparency, efficiency, and trust in banking transactions, BCT significantly improves customer attitudes towards BCT-supported banks. Furthermore, the research reveals that positive attitudes play a pivotal role in influencing customers' intentions to prefer and continue using these blockchain-backed banks. The study also highlights the importance of trust factors and transaction frequency as moderators in shaping customer attitudes and behavioral intentions in this context. The insights gleaned from this research hold practical significance for banks operating in Oman, offering guidance for tailored marketing campaigns, product design, and aligning their offerings with customer expectations in the realm of blockchain-supported banking applications. Additionally, the study provides practical recommendations for the successful implementation and adoption of blockchain-supported financial applications within the banking sector.